1962
DOI: 10.21236/ad0404878
|View full text |Cite
|
Sign up to set email alerts
|

Submarine Geology of the Tongue of the Ocean, Bahamas

Abstract: Wet Unit Weight (gn/ cc), The bulk dernlty of the edhiient-measured to the 'ecrest tenth by means at'war weight per known volume of sediment. Water Content (%): R•atio In percent of the weight of water to the weight of the dried solid particles In a given sediment mass. Void Ratio (a): The ratio between the volume of voids (Vv) and the volume of V V 5 12 t~ 'Con~ored with f IQUMe 12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1965
1965
1989
1989

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Resting unconformably upon the Eocene material was approximately a three-metre thickness of Pleistocene and Recent sediment displaying similar physical, mineralogical, and paleontological effects to those described by Busby (1962) for sediments from the Tongue of the Ocean, Bahamas. Pleistocene chronological zonation using planktonic foraminifera (Ericson et al, 1961) was attempted for this section.…”
Section: Eocene Sedimentssupporting
confidence: 54%
“…Resting unconformably upon the Eocene material was approximately a three-metre thickness of Pleistocene and Recent sediment displaying similar physical, mineralogical, and paleontological effects to those described by Busby (1962) for sediments from the Tongue of the Ocean, Bahamas. Pleistocene chronological zonation using planktonic foraminifera (Ericson et al, 1961) was attempted for this section.…”
Section: Eocene Sedimentssupporting
confidence: 54%
“…This pelagic rain is augmented by lime mud that is winnowed from the platform edge and by lime sand and carbonate rubble that are carried to the sea floor by sediment gravity flows. The resulting sedimentary deposit is made up of turbidite layers composed of rubble, sand, and silt with sharp bases and gradational tops intercalated with pelagic lime mud (Busby 1962, Rusnack and Nesteroff 1964, U.S. Navy Oceanographic Office 1967, Lynts and others 1973. Based on coring results, Rusnack and Nesteroff (1964) reported that 70 to 90 percent of the sediment in the southern TOTO cul-de-sac area was deposited by turbidity currents with a 500 to 10,000 year time span between individual turbidite events.…”
Section: Geologic Settingmentioning
confidence: 99%
“…Andrews and others (1970) and Schlager and others (1976) suggested that the high, steep slopes of TOTO result from both upbuilding of the carbonate platform and erosional deepening of the basin. Large-scale erosion in TOTO is indicated by the V-shaped axial valley, the rounded boulders, rippled coarse sand on the floor of the valley, and erosional boundary escarpments of Miocene chalk (Andrews and others 1970, Busby 1962, Gibson and Schlee 1967, Schlager and others 1976. The axial valley begins at approximately 24~ as a narrow channel and progressively deepens and widens to the north.…”
Section: Geologic Settingmentioning
confidence: 99%
“…The sediments in the Tongue of the Ocean have been studied by several authors (Athearn, 1962;Busby, 1962;Rusnak and Nesteroff, 1964;Pilkey and Rucker, 1966;Gibson and Schlee, 1967;Andrews et al, 1970 Rusnak and Nesteroff (1964) described several bioclastic turbidites recovered in their piston and gravity cores from throughout the Tongue of the Ocean, including localities a few kilometers to the southwest of Site 98. Their survey indicated that 70 to 90 per cent of the modern sediments were laid down by turbidity currents.…”
Section: Geology Of the Bahama Channelsmentioning
confidence: 99%